Components in flicker detection - Sharanjeet-Kaur (Universiti Kebangsaan Malaysia, 1996)
This study was conducted to see if slow test presentations of 1 Hz was detected by the chromatic system and higher rates of flicker of 25 Hz, 33 Hz and 40 Hz were detected by the pure flicker system at lower and higher background luminances. Spectral sensitivity measurements were carried out using a 1.2 degree test spot presented at a rate of 1 Hz, 25 Hz, 33 Hz and 40 Hz on a white background. The background luminance used were 100 td, 250 td, 500 td, 750 td, 1000 td, 2500 td and 4000 td. The study showed that the detection of a 1 Hz test is possible by 2 mechanisms, the chromatic system at high background luminance and the achromatic and chromatic systems at low background luminance. In the case 25 Hz, it is not entirely detected by the 'pure flicker system' and the transient achromatic system might contribute in its detection. Flicker rates of 33 Hz and higher are detected by the pure flicker system.